A multiple-sensitivity Hall sensor featuring a low-cost temperature compensation circuit. (July 2021) - Mo, Shaoqing; Wei, Rongshan; Zeng, Zhuoqu; He, Minghua
Abstract: An integrated Hall sensor with a 100-kHz signal-sensing bandwidth suitable for current measurements is proposed in this paper. By combining feedback technology and the bandgap compensation principle, the temperature drift of the proposed Hall sensor is compensated. Α 0.095%/°C temperature drift can be achieved over a temperature ranging from −40 ​°C to +125 ​°C. The proposed Hall sensor is implemented using 180-nm CMOS technology. The overall chip size is 3 ​mm 2, with a total current consumption of 7 ​mA at a 3.3-V supply voltage. Experimental chip measurements demonstrate that the proposed Hall sensor is capable of achieving an equivalent magnetic-field noise density of 114 nT / H z and a linearity error of 1.5%.